Self-regulation and play: how children's play directed with executive function and emotion regulation - BALABAN DAĞAL, ASUDE (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
The associations of children's play behaviour to their emotional regulation, executive functioning were examined in this study. Teachers rated children's play behaviour, emotional regulation and executive functioning. The study sample comprised 127 (Mage in months = 60.685, SD = 9.563; 64 girls) Turkish children who continued formal education in the preschools. The data is gathering by information survey, CHEXI, ERC, and Play Behaviour Scale. The results suggest that children's reticence behaviour, solidarity play, and social play are moderated by executive function and emotion regulation. Furthermore, there are several meaningful associations between each play behaviour and emotion regulation and executive function. Lastly, there are significant differences in children's executive function, parellal play, and rough and tumble play in terms of their sex.
Keywords: Play; executive function; emotion regulation; self-regulation; PRETEND-PLAY; TUMBLE PLAY; PEER PLAY; BEHAVIOR; PRESCHOOLERS; ROUGH; COMPETENCE